Biomechanical effect of vibration on a fused lumbar spine with different stabilisers. Issue 1 (24th February 2023) - Fan, Wei; Zhang, Chi; Zhao, Dan; Guo, Li-Xin
Abstract : This study aimed to compare the effects of whole-body vibration on the biomechanics of a fused lumbar spine with different posterior stabilisers, including an interspinous process spacer (IPS) and a bilateral pedicle screw system (BPSS). A finite-element model of lumbar interbody fusion with an IPS or a BPSS at the L4–L5 level was constructed based on a healthy human whole lumbar spine. Transient dynamic and static analyses were employed to compute the dynamic responses of deformation and stress for the models to a sinusoidal axial vibration load of ±40 N and its corresponding static axial loads (−40 and 40 N), respectively. The results showed that for both the IPS and BPSS models, the vibration amplitudes of the responses were significantly higher than the corresponding changing amplitudes under static loads. The increasing effect of vibration load on endplate stress at L4–L5 reached 128.3 and 146.0% for the IPS and BPSS models, respectively. In contrast, the increasing effects of vibration load on disc bulge and annulus stress at adjacent L3–L4 were nearly the same for these two models. This indicates that the vibration sensitivity of a fused level is lower when using an IPS compared with that when using a BPSS, but there is no obvious difference in the vibration sensitivity of the adjacent level when using these two stabilisers.